Influence of residual pockets on periodontal tooth loss: a retrospective analysis - Muhammad H. A. Saleh; Debora R. Dias; Obada Mandil; Ricardo Puziol de Oliveira; Abdusalam Alrmali; Maurício G. Araújo; Hom‐Lay Wang; Zoltán Baráth; István Urbán (2023)
Abstract Background Individuals enrolled in supportive periodontal therapy ( SPT ) can still present with tooth loss due to periodontitis (TLP). There is limited evidence on the influence of residual pockets (RPc) and a defined “threshold” at which a patient's profile is set to be at high risk for TLP in the literature. Therefore, this study aimed to assess the influence of RPc on TLP and determine the prognostic performance of RPc compared to the staging and grading of periodontitis on TLP risk. Methods Clinical data from 168 patients (3869 teeth) treated for periodontitis and receiving SPT for at least 10 years were evaluated in this retrospective study. TLP and the percentage of sites with RPc ≥ 5 mm or ≥6 mm per patient were collected. The prognostic performance of RPc was compared to the staging and grading of the disease on TLP using a multilevel Cox proportional hazard regression model. Results Over a median follow‐up of 25 years, 13.7% of teeth were lost, 4.6% of which were due to periodontitis. Most patients with TLP had ≥1 site with RPc ≥5 mm (90.8%) or ≥6 mm (77.6%). Multivariate multilevel Cox regression revealed that patients with >15% of sites with RPc ≥5 mm had a hazard ratio of 2.34, and grade C had a hazard ratio of 4.6 for TLP compared to RPc ≤4 mm/grade A. Grading exhibited the best discrimination and model fit. Conclusion Patients with RPc ≥5 mm at >15% of the sites are at risk for tooth loss. Grading and RPc ≥5 mm displayed very good predictive capability of TLP.